FUNGSI BAHASA PADA KAOS DI KALANGAN REMAJA - Markub Markub (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
Language as a communication tool plays a very important role in human life because human language can interact and talk about anything. Language as a tool to convey thoughts, ideas, concepts, or feelings. An intellectual must think and the process of thinking definitely requires language. Language also functions as a means for social interaction and the media conveys ideas, the purpose of this study is to describe the function of language in counsels among adolescents. The method used in this study is a qualitative descriptive method. The data in this study are various languages ​​including the form of language, language functions, and the meaning of expressions. The form of language in the form of words, phrases, clauses, and sentences. Language functions in the form of expression functions, information functions, exploration functions, persuasion functions, entertainment functions, Data sources in this study are the function of language on shirts among teenagers. The technique used in this data collection is documentation, see, and note. The results of research on the function of shirts on teenagers that the function of language is a tool of social interaction, as a medium for conveying ideas, concepts, thoughts, and expressions of feelings including expression functions, information functions, exploration functions, persuasion functions, and entertainment functions on shirts. among teenagers.